MEMPERKUAT LITERASI DIGITAL GURU PAUD DALAM PERAN MANAJEMAN KEPALA SEKOLAH BERBASIS INFORMASI TEKNOLOGI (IT) DI RA SHIROTUL JANNAH GONDANGLEGI-MALANG - Jamila, Isnaini Fauzia (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
Principal management plays an important role in strengthening teachers' digital literacy skills. Principals as headmasters are able to process the resources they have for programs to strengthen digital literacy for PAUD teachers. This research uses a qualitative research method with a case study approach. With the Miles and Huberman data analysis model. The research results revealed that the management carried out by the school principal was a program to strengthen teachers' digital literacy through Microsoft Word and Microsoft Excel applications. The suggestion for school principal management in the teacher digital literacy strengthening program is that the teacher digital literacy strengthening program be further developed, not only in developing the ability to use Microsoft Word and Microsoft Excel applications but also in the use of digital media in children's learning processes, such as the use of videos. digital, power point and various online applications that can be used in children's learning process. So that children have a religious learning experience and can be introduced to digital learning from an early age, with the hope that children can know the positive side of using digital media in everyday life.